Sustainability Performance and Financial Performance Relationship: The Moderating Effect of CEO Tenure - Anita Anita; Khelly Khelly (Jurnal Manajemen Dan Akuntansi Medan, 2026)
This study investigates whether CEO tenure moderates the relationship between sustainability performance and financial performance among companies listed on the Indonesian Stock Exchange. Sustainability performance is measured using disclosure indicators aligned with the Global Reporting Initiative Standards, while financial performance is proxied by return on assets and return on equity. Using panel regression analysis with firm level observations, the results show that sustainability performance has a significant positive effect on financial performance in both measurements. This indicates that firms with stronger sustainability performance tend to achieve higher profitability and better returns for shareholders, potentially due to improved transparency, stakeholder trust, and reputational benefits. However, CEO tenure does not moderate the relationship between sustainability performance and financial performance when financial performance is measured using return on assets and return on equity. This suggests that the positive association between sustainability performance and financial outcomes is relatively consistent across firms led by CEOs with shorter or longer tenures. The findings contribute to the ongoing debate on the financial relevance of sustainability initiatives and highlight that sustainability performance can be value relevant in the Indonesian context. Practically, the results imply that companies may enhance financial outcomes by strengthening sustainability performance, while changes in CEO tenure alone may not alter the sustainability performance to financial performance linkage.